Patterns of Exclusion: Sanitizing Space, Criminalizing Homelessness - Amster, Randall (Social justice, 2003)
Part of a special issue on race, security, and social activism in the U.S. A study was conducted to attempt to locate contemporary manifestations of patterns of marginalization and spatial exclusion of the impoverished within their historical contexts. Data were drawn from a theoretical overview of anti-homeless legislation and regimes of spatial control combined with observation of actual events and activities. Findings demonstrated the demonized existence of the homeless as constant targets of regulation, criminalization, expulsion, and erasure.